Understanding meaning-making of diversity : education students' experience of a 10 day intensive programme - Pardede, Saga (2017)
The aim of this study is to question meaning-making and how individuals’ narrate around it based on a 10 day intensive programmes. Inside out - Outside in: Building bridges with diversity in teacher education project was the focused of research, based on the collaboration of eight universities invested in teacher education that took place in the University of Jyväskylä. Thirty-two participants’ were involved sharing their experiences and stories based on two sets of data; 1) pre-questionnaire and, 2) a final reflective essay in response to the programme. A thematic analysis was used for the first data set, and a dialogic analysis was used for the second set of data. Four major themes emerges out of the first data set in correspond to participants’ meaning-making of previous learning experiences and understanding of diversity, suggesting an experience in reference to ‘habits’ or ‘authenticity’ – dialogic. Second data set highlights elements of ‘internally persuasive’ and ‘externally authoritative’ discourse involving the participants’ meaningful experiences and final reflective essay. The overall findings of both data suggest that the relationship between theory and practice is problematic. Moreover, learning is an ongoing process that reshapes our perspectives and beliefs. During this process, participants’ attach meanings to their experiences which correspond with their dialogic and monologic nature with regard to the notion of meaning-making. To conclude, this study presents a dialogic approach towards recognising the participants’ meaning-making journey, in addition a meaningful inside concerning pre-service teacher education in relation to repertoires, awareness and understanding of diversity within the education systems.